(untitled) (Journal of Face Aesthetics, 2024)
On November 24, 2023, a Scientific and Training conference entitled: "Weariness – its role and influence on facial appearance" under the patronage of: Magnificence Rector of the Poznań Medical University prof. Andrzej Tykarski, Supreme Medical Chamber, Mayor of Poznań and Greater Poland Medical Chamber. The conference was opened by the President of the Greater Poland Medical Chamber, Dr. Krzysztof Kordel.